Pensamento, linguagem e língua escrita segundo a epistemologia genética processos e construções análogos - Sasso, Bruna Assem (Editora Oficina Universitária, 2020)
Despite finding productions on literacy, including under the theoretical framework of Emilia Ferreiro, none was found that sought to relate the development of thought, language and written language from the perspective of genetic epistemology. Thus, the intention of this book is to address child development and the psychogenesis of written language beyond the "phases" or "writing hypotheses". What does the acquisition of written language have to do with the acquisition of oral language and thought? Would there be relationships? What are the processes: how does it happen and why does it happen in such ways? What's behind it? That's what this book is about. May this book generate reflections, reaching and helping parents, teachers, researchers and the like regarding aspects of child development in Basic Education, literacy in the early years of Elementary Education, providing a theoretical basis for discussions and conscious and intentional educational practices for/about the processes intrinsic to the development of subjects.